Diabetes MILES Youth–Australia: methods and sample characteristics of a national survey of the psychological aspects of living with type 1 diabetes in Australian youth and their parents. Issue 1 (December 2016) - Hagger, Virginia; Trawley, Steven; Hendrieckx, Christel; Browne, Jessica; Cameron, Fergus; Pouwer, Frans; Skinner, Timothy; Speight, Jane
Abstract Background Type 1 diabetes is a complex and demanding condition, which places a substantial behavioural and psychological burden on young people and their families. Around one-third of adolescents with type 1 diabetes need mental health support. Parents of a child with type 1 diabetes are also at increased risk of psychological distress. A better understanding of the motivators, behaviours and psychological well-being of young people with diabetes and their parents will inform improvement of resources for supporting self-management and reducing the burden of diabetes. The Diabetes MILES (Management and Impact for Long-term Empowerment and Success) Youth–Australia Study is the first large-scale, national survey of the impact of diabetes on the psychosocial outcomes of Australian adolescents with type 1 diabetes and their parents. Methods/design The survey was web-based to enable a large-scale, national survey to be undertaken. Recruitment involved multiple strategies: postal invitations; articles in consumer magazines; advertising in diabetes clinics; social media (e.g. Facebook, Twitter). Recruitment began in August 2014 and the survey was available online for approximately 8 weeks. A total of 781 young people (aged 10–19 years) with type 1 diabetes and 826 parents completed the survey. Both genders, all ages within the relevant range, and all Australian states and territories were represented, although compared to the general Australian population of youth with type 1 diabetes, respondents were from a relatively advantaged socioeconomic background. Discussion The online survey format was a successful and economical approach for engaging young people with type 1 diabetes and their parents. This rich quantitative and qualitative dataset focuses not only on diabetes management and healthcare access but also on important psychosocial factors (e.g. social support, general emotional well-being, and diabetes distress). Analysis of the Diabetes MILES Youth–Australia Study data is ongoing, and will provide further insights into the psychosocial problems facing young people with type 1 diabetes and their parents. These will inform future research and support services to meet the needs of young Australians with type 1 diabetes and their families.